PENGARUH DOSIS PUPUK NITROGEN TERHADAP PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS PADI GOGO (Oryza sativa L) - Fiator Nong (Fakultas Pertanian, Universitas Nusa Nipa, 2022)
Upland rice is one of the plant varieties that are widely cultivated by the community in general. Nitrogen is an important nutrient for plant growth, as an element that forms proteins, nucleic acids and other important compound. To obtain high production, nitrogen fertilization is needed. Plants only take up part of the nitrogen from the nitrogen fertilizer given to the soil, while the rest is used by microorganisms and is lost due to leaching or evaporation of nitrogen gases. This study used a Randomized Block Design (RAK), with a factorial treatment arrangement. The treatments tested were nitrogen fertilization doses consisting of 4 levels, namely NO = without fertilizer, N1 = 45 kg N ha-1 (97.8 kg urea ha-1), N2 = 90 kg N ha-1 (195.6 kg urea ha-1), N3 = 135 kg N ha-1 (293.5 kg urea ha-1) and the second factor was upland rice varieties consisting of 3 varieties, namely VL = Manukaya Local Variety, VT = Towuti Variety, VSB = Situ Bagendit Variety. The stages of this research were land preparation, planting, fertilization, weeding, harvesting and observation. The interaction between the nitrogen (N) dose treatments had a very significant effect on growth variables (plant height, number of leaves, number of tillers, leaf area index). Interaction also has a very significant effect on the yield components (tillers, productive, number of panicles in clump-1, panicle length, number of grains in panicle-1, dry weight of the stover, oven ha-1. The highest yield of oven dry weight ha-1 achieved in each variety is the Local Manukaya variety 3.315 t ha-1 (N2) at a nitrogen fertilizer dose of 90 kg N ha-1. In the Towuti variety, the highest oven dry grain yield is 3.851 t ha-1 with a nitrogen fertilizer dose of 135 kg N ha-1 (N3). In the Situ Bagendit variety, the highest oven dry grain yield is 3.952 t ha-1 at a fertilizer dose of 135 kg N ha-1 (N3).